Rapid Evaluation Methods for Quality of Trout (Oncorhynchus mykiss) Fresh Fillet Preserved in an Active Edible Coating - Maria Grazia Volpe; Elena Coccia; Francesco Siano; Michele Di Stasio; Marina Paolucci (Foods, 2019)
In this study different methods were used to evaluate the effectiveness of a carrageenan coating and carrageenan coating incorporating lemon essential oil (ELO) in preserving the physicochemical and olfactory characteristics of trout fillets stored at 4 °C up to 12 days. The fillet morphological structure was analyzed by histological and immunological methods; lipid peroxidation was performed with the peroxide and thiobarbituric acid reactive substances (TBARS) tests. At the same time, two less time-consuming methods, such as Attenuated Total Reflectance-Fourier Transformed Infrared (ATR-FTIR) spectroscopy and the electronic nose, were used. Uncoated trout fillets (UTF) showed a less compact tissue structure than carrageenan-coated threads (CTF) and coated fillets of carrageenan (active) ELO (ACTF), probably due to the degradation of collagen, as indicated by optical microscopy and ATR-FTIR. UTF showed greater lipid oxidation compared to CTF and ACTF, as indicated by the peroxide and TBARS tests and ATR-FTIR spectroscopy. The carrageenan coating containing ELO preserved the olfactory characteristics of the trout fillets better than the carrageenan coating alone, as indicated by the electronic nose analysis. This study confirms that both carrageenan and ELO containing carrageenan coatings slow down the decay of the physicochemical and olfactory characteristics of fresh trout fillets stored at 4 °C, although the latter is more effective.